The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2003
DOI: 10.2527/2003.8151185x
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid sequences of multiple fast and slow troponin T isoforms expressed in adult bovine skeletal muscles

Abstract: Multiple nucleotide sequences of complementary DNA (cDNA) of bovine troponin T (TnT) isoforms expressed in the adult skeletal muscles were determined to facilitate the elucidation of the TnT degradation progress during postmortem aging of muscles. Fresh muscle samples were excised from the lingual, masseter, pectoralis, diaphragm, psoas major, longissimus thoracis, spinnalis, semitendinosus, semimembranosus, and biceps femoris muscles of three Holstein cows within 1 h of slaughter. Complementary DNA fragments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…The levels of expression of the other six were unchanged or decreased in DM and H muscles. These fTnT isoforms differ in terms of the presence of the alternative splicing region corresponding to mutually exclusive exons 16 and 17 , Muroya et al, 2003. All these data demonstrated that the TnT fast isoforms over-expressed in the muscle of high muscle growth potential (DM and H) contained the exon 16 and the others contain the exon 17.…”
Section: Comparison Of Gene Expression Between Muscle Typesmentioning
confidence: 73%
“…The levels of expression of the other six were unchanged or decreased in DM and H muscles. These fTnT isoforms differ in terms of the presence of the alternative splicing region corresponding to mutually exclusive exons 16 and 17 , Muroya et al, 2003. All these data demonstrated that the TnT fast isoforms over-expressed in the muscle of high muscle growth potential (DM and H) contained the exon 16 and the others contain the exon 17.…”
Section: Comparison Of Gene Expression Between Muscle Typesmentioning
confidence: 73%
“…These two isoforms are grouped in cluster 5, which displayed up-regulated proteins at 260 dpc. Fast TnT isoforms proteins are also the product of a complex alternative splicing (Muroya et al, 2003;Bouley et al, 2004). Our results displayed four different isoforms of fTnT according to their pI and MW.…”
Section: Discussionmentioning
confidence: 89%
“…According to these authors, these two slow TnT isoforms are the product of alternative splicing of the murine exon 5 (Huang et al, 1999). The most acidic one is referred to as sTnT1 by Muroya et al (2003) and the most basic one is referred to as sTnT2. These two isoforms are grouped in cluster 5, which displayed up-regulated proteins at 260 dpc.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, Whipple and Koohmaraie (1992) examined the amount of post-mortem proteolysis in three different lamb muscles and concluded that degradation products derived from TnT in supraspinatus, a slow type muscle, were distinct from those in longissimus and gluteus medius, fast type muscles. On the other hand, Muroya, Nakajima, and Chikuni (2003), established that slow-oxidative muscles were richer in slow TnT isoforms than were the fast muscles. In this study, 25 fragments of fast TnT have been identified against only two slow TnT fragments.…”
Section: Contribution Of Endopeptidases: Cathepsins and Calpainsmentioning
confidence: 98%